Genome-wide analysis reveals regulatory mechanisms and expression patterns of TGA genes in peanut under abiotic stress and hormone treatments - Zhong, Chao; Liu, Yu; Li, Zhao; Wang, Xiaoguang; Jiang, Chunji; Zhao, Xinhua; Kang, Shuli; Liu, Xibo; Zhao, Shuli; Wang, Jing; Zhang, He; Huang, Yuning; et al. (Frontiers in Plant Science, 2023)
The TGA transcription factors, plays a crucial role in regulating gene expression. In cultivated peanut (Arachis hypogaea), which faces abiotic stress challenges, understanding the role of TGAs is important. In this study, we conducted a comprehensive in analysis of the TGA gene family in peanut to elucidate their regulatory mechanisms and expression patterns under abiotic stress and hormone treatments. The genome-wide analysis revealed that a total of 20 AhTGA genes were identified and classified into five subfamilies. Collinearity analysis revealed that AhTGA genes lack tandem duplication, and their amplification in the cultivated peanut genome primarily relies on the wholegenome duplication of the diploid wild peanut to form tetraploid cultivated peanut, as well as segment duplication between the A and B subgenomes. Promoter and Protein-protein interaction analysis identified a wide range of cis-acting elements and potential interacting proteins associated with growth and development, hormones, and stress responses. Differential expression patterns of AhTGA genes in different tissues, under abiotic stress conditions for low temperature and drought, and in response to hormonal stimuli revealed that seven AhTGA genes from groups I (AhTGA04, AhTGA14 and AhTGA20) and II (AhTGA07, AhTGA11, AhTGA16 and AhTGA18) are involved in the response to abiotic stress and hormonal stimuli. The hormone treatment results indicate that these AhTGA genes primarily respond to the regulation of jasmonic acid and salicylic acid. Overexpressing AhTGA11 in Arabidopsis enhances resistance to cold and drought stress by increasing antioxidant 2 This is a provisional file, not the final typeset article activities and altering endogenous hormone levels, particularly ABA, SA and JA.The findings provide insights into peanut's abiotic stress tolerance mechanisms and pave the way for future functional studies.